DIRECTIVE SPEECH ACT IN THE FILM "SUPER IRIT FAMILY" DIRECTED BY DANIAL RIFKI - Della Ardila; Alber Alberb (SOSIOEDUKASI, 2026)
This study aims to identify and describe the form and function of directive speech in the film Keluarga Super Irit by director Danial Rifki, as well as reveal the influence of gender on the communication patterns of the characters in the film. The method used in this study is descriptive qualitative with a content analysis approach. The source of data in this study is the film Keluarga Super Irit which lasts 116 minutes, with data in the form of speech that contains elements of directive speech and gender perspectives. The data collection technique is carried out through documentation, listening, and recording techniques. The data analysis refers to the theory of directive speech form Ibrahim (1993) and the sociopragmatic theory of gender Prayitno (2017). The results of the study showed that there were 87 data on directive speech actions divided into six forms, namely: command (31 data), question (18 data), request (16 data), advice (14 data), prohibition (5 data), and granting permission (3 data). The dominance of the act of speaking commands shows that instruction is the main driver of the narrative in the film. From a gender perspective, a contrasting pattern was found between male and female speakers. Female speakers dominated the categories of differences in the form of language use (18 data), language attitudes (15 data), and the nature and manner of language (11 data), which reflected the use of specific, meticulous, and expressive diction to maintain domestic harmony. In contrast, male speakers showed strong dominance in the aspect of differences in language attitudes (26 data) that represented rational, assertive, and authoritative communication styles. This study concludes that the act of directive speech in the film is a means of representation of gender ideology, where men tend to prioritize the efficiency of actions, while women focus more on maintaining emotional relationships and family stability.